2010
DOI: 10.1186/1471-2164-11-92
|View full text |Cite
|
Sign up to set email alerts
|

Identification of arginine- and lysine-methylation in the proteome of Saccharomyces cerevisiae and its functional implications

Abstract: BackgroundThe methylation of eukaryotic proteins has been proposed to be widespread, but this has not been conclusively shown to date. In this study, we examined 36,854 previously generated peptide mass spectra from 2,607 Saccharomyces cerevisiae proteins for the presence of arginine and lysine methylation. This was done using the FindMod tool and 5 filters that took advantage of the high number of replicate analysis per protein and the presence of overlapping peptides.ResultsA total of 83 high-confidence lysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(100 citation statements)
references
References 82 publications
5
93
2
Order By: Relevance
“…MK motif appears to be evolutionarily conserved through eukaryotic cells, and Pang et al also noticed the same motif for methylated lysine from a much smaller protein data set in Saccharomyces cerevisiae. 28 Lysine and arginine methyltransferases seem to have distinct protein target specificities. In contrast to arginine methylation, we Normal (normal medium-cultured sample) and heavy ( 13 CD 3 -methionine medium-cultured sample), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…MK motif appears to be evolutionarily conserved through eukaryotic cells, and Pang et al also noticed the same motif for methylated lysine from a much smaller protein data set in Saccharomyces cerevisiae. 28 Lysine and arginine methyltransferases seem to have distinct protein target specificities. In contrast to arginine methylation, we Normal (normal medium-cultured sample) and heavy ( 13 CD 3 -methionine medium-cultured sample), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Methylation of proteins and RNAs is a widespread modification known to modulate their functions (42,48,65). Trm112 activates several class I SAM-dependent MTases with substrates implicated in translation, such as several tRNAs (modified by Trm9 and Trm11), and the eukaryotic release factor 1 (by Mtq2).…”
Section: Discussionmentioning
confidence: 99%
“…2A, GATA4 was robustly methylated by wild-type PRMT5, but not by PRMT5 mutant, indicating that GATA4 is in fact a good substrate for PRMT5. Previous studies have shown that arginine residues in the RXG motif and the sequences containing proline at either or both of these positions X(P)RXXX(P) were significantly favored to be methylated by arginine methyltransferase (27,28). To pinpoint the PRMT5-mediated methylation sites in GATA4, we examined the protein sequence of GATA4 and identified the arginine residues at positions of 229 (Arg-229), 265 (Arg-265), and 317 (Arg-317) as potential sites (Fig.…”
Section: Prmt5mentioning
confidence: 99%